(untitled) (Annals of Medical Research, 2021)
Aim: The aim of this study was to assess the effects of playing digital games on the pain levels and mobility states of children post-angiography.Material and Methods: This randomized controlled trial was carried out at the pediatric cardiology clinic at a tertiary care hospital in eastern Turkey between October 2016 and July 2017. Eighty children (n=40 digital game group, n=40 control group) post-angiography were randomized. Children in the experimental group played digital games. Wong–Baker FACES pain rating scale (WBFS) and in-bed movement form were used.Results: TThe difference between the means pretest WBFS scores of the digital game group and control group children was not significant (t=1.29; p>0.05). The difference between the mean posttest WBFS scores of the digital game group and control group children was statistically significant (t=9.63; p0.01). The mean number of in-bed movements was 2.45±1.53 in the digital game group and 13.25±18.92 in the control group. The difference between two groups in total mean number of in-bed movements was significant (p0.01).Conclusion: For children who are post-angiography, playing digital games decreased pain levels and mobility states.